Unilateral plyometric training effectively reduces lower limb asymmetry in athletes: a meta-analysis - Sun, Wei; Li, Hui; Qu, Luping; Zhou, Yuehui; Cao, Xiaoyang; Wang, Ke; Li, Ke (Frontiers in Physiology, 2025)
BackgroundLower limb asymmetry in athletes is associated with impaired performance and elevated injury risk. Plyometric training (PT) and complex training (CT) are commonly used interventions for this problem, but existing evidence on their effectiveness remains inconsistent.ObjectiveThis meta-analysis aimed to evaluate PT and CT’s effects on athletes’ lower limb asymmetry. The findings could help optimize training protocols and reduce the risk of sports injuries.MethodsA systematic search of Web of Science, PubMed, ProQuest, Scopus, EBSCO, CNKI, and Wanfang databases was conducted up to March 2024. Two researchers independently performed the literature screening, data extraction, and quality assessment processes. A meta-analysis was conducted via Review Manager 5.3 software, including heterogeneity tests, effect size pooling, subgroup analysis, and funnel plot construction.ResultsA total of eight randomized controlled trials (RCTs) involving 157 participants were included. PT effectively reduced lower limb asymmetry, particularly improving single-leg countermovement jump (SLCMJ) (SMD = 0.51, P = 0.05), single-leg broad jump (SLBJ) (SMD = 0.56, P = 0.01), and single-leg lateral jump (SLLJ) (SMD = 1.24, P = 0.01), but did not affect single-leg horizontal triple jumps (SLH3J) (SMD = 0.24, P = 0.60). In contrast, CT showed no meaningful reduction in asymmetry. Subgroup analysis indicated that unilateral PT alone significantly decreased asymmetry (SMD = 0.71, P < 0.01), whereas bilateral PT (SMD = 0.23, P = 0.45), unilateral CT (SMD = −0.15, P = 0.15) and bilateral CT (SMD = −0.09, P = 0.78) interventions all failed to demonstrate efficacy.ConclusionUnilateral PT effectively reduces lower limb asymmetry in athletes. Coaches should integrate this method into training programs to address asymmetry-related performance deficits and injury risks. Further high-quality trials are required to validate clinical applicability.